2021
DOI: 10.1186/s12883-021-02365-8
|View full text |Cite
|
Sign up to set email alerts
|

Long QT syndrome with potassium voltage-gated channel subfamily H member 2 gene mutation mimicking refractory epilepsy: case report

Abstract: Background Epileptic seizures can be difficult to distinguish from other etiologies that cause cerebral hypoxia, especially cardiac diseases. Long QT syndrome (LQTS), especially LQTS type 2 (LQT2), frequently masquerades as seizures because of the transient cerebral hypoxia caused by ventricular arrhythmia. The high rate of sudden death in LQTS highlights the importance of accurate and early diagnosis; correct diagnosis of LQTS also prevents inappropriate treatment with anti-epileptic drugs (AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…As shown in Table 2, two studies reported sudden death among affected people, indicating that the gene variant has a high associated risk. 7,13,15,16,[18][19][20][21][22][23][24][25][26][27][28][29] Here, we report a family with a KCNH2 Arg 744* pathogenic variant presenting with both epilepsy and LQTS. The same variant was previously reported in patients with epilepsy or LQTS, but none of these cases had a dual phenotype of epilepsy and LQTS.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As shown in Table 2, two studies reported sudden death among affected people, indicating that the gene variant has a high associated risk. 7,13,15,16,[18][19][20][21][22][23][24][25][26][27][28][29] Here, we report a family with a KCNH2 Arg 744* pathogenic variant presenting with both epilepsy and LQTS. The same variant was previously reported in patients with epilepsy or LQTS, but none of these cases had a dual phenotype of epilepsy and LQTS.…”
Section: Discussionmentioning
confidence: 85%
“…Although the KCNH2 Arg 744* variant has been previously reported in patients with epilepsy or LQTS, none of these cases had a dual phenotype of epilepsy and LQTS (Table 2). As shown in Table 2, two studies reported sudden death among affected people, indicating that the gene variant has a high associated risk [7,13,15,16,[18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…LQTS characteristically manifests with an EKG finding of torsades de pointes and presents with syncope or sudden cardiac death. It frequently masquerades as epilepsy in its presentation, and sudden death from LQTS also mimics sudden unexpected death in epilepsy (SUDEP) 3–5 . Apart from cardiac tissues, the ion channels of LQT are also identified in non‐cardiac tissues 2 …”
Section: Figurementioning
confidence: 99%
“…It frequently masquerades as epilepsy in its presentation, and sudden death from LQTS also mimics sudden unexpected death in epilepsy (SUDEP). [3][4][5] Apart from cardiac tissues, the ion channels of LQT are also identified in non-cardiac tissues. 2 We report a case of a 33-year-old female who presented to the epilepsy clinic with a history of recurrent episodes…”
mentioning
confidence: 99%
“…In the brain, Kv11.1 regulates neuronal excitability and has been associated with seizure and epilepsy 2731 . However, as patients with LQTS often experience syncope accompanied by a non-epileptic seizure, they are frequently misdiagnosed with epilepsy and incorrectly treated with anti-seizure medications 28,32,33 .…”
Section: Introductionmentioning
confidence: 99%